Public Services in the Raskin Program: Evaluation in Damai Bahagia Subdistrict, South Balikpapan - Murdelina; Aji Ratna Kusuma; Santi Rande; Zekeri Momoh (Universitas Muhammadiyah Makassar, 2026)
Persistent urban poverty and uneven food assistance delivery continue to challenge equitable public service provision in Indonesian cities. This study evaluates public service delivery in the Raskin Program in Damai Bahagia Subdistrict, South Balikpapan, with specific attention to service procedures, targeting accuracy, distribution transparency, and beneficiary satisfaction. A descriptive qualitative design was applied through in-depth interviews with local officials, program implementers, community representatives, and beneficiary households, supported by direct observation and document review. Data were analyzed using an interactive qualitative model involving data reduction, data display, and conclusion drawing, with source and method triangulation to strengthen credibility. The findings show that the program reached low-income beneficiaries and was supported by positive staff attitudes and responsive interpersonal service. However, its effectiveness was constrained by unclear procedures, limited information access, distribution delays, uneven transparency, and weak beneficiary-data updating, which increased the risk of inclusion and exclusion errors. The study concludes that food assistance effectiveness depends on local administrative capacity, procedural clarity, data governance, and accountability mechanisms. The novelty of this study lies in integrating service quality, targeting accuracy, transparency, and satisfaction in a localized urban Raskin evaluation. The findings contribute to public service and social assistance governance by offering empirical insights for improving equitable, transparent, and accountable food assistance delivery.